Peran Agen (PT. Seroja Jaya) dalam Penerbitan Port Health Clearance Kapal Asing melalui Sistem SINKARKES - Situmorang, Lamsar Pahalatua; Ginting, Suratni; Sahid, Muhammad (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research aims to examine the contribution of PT. Seroja Jaya Agensi in the PHQC issuance mechanism, while also identifying obstacles and alternative solutions in the implementation of the INSW system in Bojonegara. The issuance of Port Health Quarantine Clearance (PHQC) based on the Indonesia National Single Window (INSW) system at the Bojonegara Health Quarantine Office is a vital aspect in efforts to control the health risks of foreign vessels entering Indonesian waters. The role of agencies, especially PT. Seroja Jaya Agensi Merak Branch, is crucial in ensuring the smoothness of the PHQC issuance procedure in accordance with applicable regulations. This agency activity includes coordination between the ship, health quarantine officers, and other authorized institutions to ensure that incoming vessels are free from the threat of infectious diseases. During the onshore practice, the author collected data using field research and literature study methods, by reviewing journals and other relevant sources that support the study theme. The results of the study show that the agency's role is quite crucial in supporting smooth administration, although there are still problems related to inter-agency coordination and technical understanding of INSW that need to be improved. This research is expected to contribute positively to improving the health surveillance system for foreign vessels, particularly to optimize the implementation of INSW for greater effectiveness.